Quality assessment: Adaptation of Mexican sports context CECASDEP by delphi method - Morquecho Sánchez, Raquel; Medina Rodríguez, Rosa Elena; Morales Sanchéz, Verónica; Ramos Carranza, Isela Guadalupe (2013)
The sports management through quality becomes an indispensable tool for any sport organization that seecks to stand out and be benchmarck in the field of sport...